Public health aspects of the house fly, Musca domestica L. (Diptera: muscidae) - Enterococcus spp. association - Akhtar, Mastura (Kansas State University, 2008)
House fly (Musca domestica L.) larvae develop in decaying organic substrates such as animal manure and adult flies likely play an important role in the ecology of fecal bacteria, including potentially virulent strains. House fly larval development strictly depends on an active bacterial community in the habitat. Although the principle of this symbiosis is not well understood, this association plays a fundamental role in transmission of microbes by this insect. In this study, enterococci were chosen as a model organism to assess the role of house flies in dissemination of multi-drug resistant bacteria in the agricultural environment. House flies (FF) and cattle manure (FM) from a cattle feedlot (frequent use of antibiotics) and house flies (BF) and manure of the American bison (BM) from the Konza Prairie Nature Preserve (no antibiotic use) were collected and analyzed. Results showed a significantly higher prevalence of enterococci resistant to tetracycline and erythromycin in FM and FF compared to that of BF and BM. Enterococcal diversity did not indicate the house fly development in manure in the corresponding habitats but the antibiotic resistance data showed very similar profiles among isolates from flies and corresponding locations. Resistance genes (tetM, tetS, tetO, ermB) and the conjugative transposon Tn916 were the most commonly detected determinants from resistant isolates from both environments. The house fly digestive tract was evaluated for the potential for horizontal transfer of antibiotic resistance genes among Enterococcus faecalis. Horizontal transfer of the pCF10 plasmid with the tetracycline resistance gene (tetM) occurred in the fly digestive tract with a transfer rate up to 101 T/D. In addition, eight enterococcal species were selected to evaluate their role and survival during house fly development. Overall, the survival rate (egg to adult) was significantly higher with E. hirae, E. durans and E. avium compared to other strains. These results indicate: a) house flies play an important role in the ecology of antibiotic resistant enterococci; b) the house fly digestive tract provides conditions for horizontal gene transfer among enterococci, and c) enterococci support the house fly development and can colonize the gut of newly emerging adult flies.
Keywords: House fly; Enterococcus; Multidrug resistant enterococci; Antibiotic use in food animals; Horizontal transfer of resistance genes; Public health aspects of fly-enterococci symbiosis; Biology, Entomology (0353); Biology, Microbiology (0410); Health Sciences, Public Health (0573)